Requirement Model for PEKA Management System: A Case Study in Kubang Pasu Secondary Schools - Amani, Abdullah Mubarak (2006)
PEKA is Penilaian Kemahiran Amali, the Assessments of Science Process Skills. In the secondary schools, PEKA involves Science, Physics, Chemistry and Biology subjects.It is implemented in Malaysian schools to enhance the effectiveness of teaching and learning of science in schools. However, teachers are facing problems and more workload in managing and recording the PEKA results since it is conducted manually. Therefore this study is to utilise a requirement model as a basis to develop a PEKA Management System so as to assist teachers in managing PEKA assessment in schools.It is also aimed to minimize the burden shouldered by teachers in the process of recording and managing the results. The requirement model consists of use case diagrams, use case specifications, class diagrams, sequence diagrams, collaboration diagrams, activity diagrams and supporting textual information. A prototype was then developed based on these diagrammatically models which were used to validate the users' requirements. The prototype was able to auto-calculate the grades obtained by students in this assessment. Through requirement testing, 37 functional requirements and 2 non-functional requirements were validated. Thus, this study is essential in developing PEKA Management System which can reduce the problems face by the teachers in the schools or any other educational organizations.